Are We In This Together?: The Polarisation of the British Society and the Marginalisation of Otherness in Ali Smith’s Seasonal Quartet - Dobrogoszcz, Tomasz (Porównania, 2021)
Ali Smith’s seasonal quartet—Autumn, Winter, Spring, Summer—was written and published at lightning speed, between the 2016 Brexit referendum and Britain’s effective departure from the EU in 2020. The article examines how the novels engage with the issue of Brexit, as they become the chronicle of a grinding cultural process and critically confront the transformation of the British nation. I survey various psychological factors related to the polarisation of the British nation and investigate Smith’s presentation of the way in which the populist propaganda of menace produced by the right-wing media leads to marginalising Otherness. Employing the nomadic theory of the subject developed by Rosi Braidotti, I analyse Smith’s literary strategies used to represent not only post-truth manipulation and institutionalised British xenophobia, but also the actions of people who resist them.